Guideline Development of Student Care and Support Operation System Effective of Schools Under Lopburi Primary Educational Service Area Office 2: การศึกษาแนวทางการพัฒนาการดำเนินงานตามระบบดูแลช่วยเหลือนักเรียน ที่มีประสิทธิภาพของสถานศึกษาในสังกัดสำนักงานเขตพื้นที่การศึกษา ประถมศึกษาลพบุรี เขต 2 - Seephasen, Chatree (Journal of Graduate MCU KhonKaen Campus, 2022)
The objectives of this research were: (1) to study needs and necessities of the implementation of student support system of schools under Lopburi Primary Educational Service Area 2 and (2) to study the development guidelines for the implementation of Student Support System. of schools under Lopburi Primary Educational Service Area 2. The sample group used in this research were school administrators and teachers in charge of student support system of schools under Lopburi Primary Educational Service Area 2 from educational under Lopburi Primary Educational Service Area 2. Number of 103 locations. The tools used in this data collection as an interview and a questionnaire on the present and desirable conditions of the implementation of student support system of schools under Lopburi Primary Educational Service Area 2. The statistics used in the data analysis were hundred percent, mean, standard deviation. and content analysis. The results of research were found that: (1) The current condition of the student support system operation of schools under Lopburi Primary Educational Service Area 2, overall was at a high level in all aspects, (2) Requirements for implementing the student support system of schools under Lopburi Primary Educational Service Area Office 2, overall it's at a very at high level and (3) guidelines for developing the implementation of the effective student support system of educational under Lopburi Primary Educational Service Area 2, presented in 5 aspects as follows: (1) The aspect of knowing students individually is carried out by collecting student data using various methods using various tools, (2) Student screening is carried out by considering the information on the students' family behavior, (3) The school promotes activities that help develop and promote students, (4) Prevention and problem solving by providing initial counseling and activities to prevent and solve problems, follow up and help and (5) Referring students to carry out by teachers, counselors, coordinating administrative teachers and guidance teachers out-of-school referrals for students with problems beyond the ability of teachers to develop.